Entrepreneurial orientation, competitive advantage, and SMEs’ performance: application of firm growth and personal wealth measures - Kiyabo, Kibeshi; Isaga, Nsubili (Journal of Innovation and Entrepreneurship, 2024)
A research article submitted to the Journal of Innovation and Entrepreneurship